Protective Roles of Apigenin Against Cardiometabolic Diseases: A Systematic Review - Xu, Yajie; Li, Xue; Wang, Hui (Frontiers in Nutrition, 2022)
Apigenin is a flavonoid with antioxidant, anti-inflammatory, and anti-apoptotic activity. In this study, the potential effects of apigenin on cardiometabolic diseases were investigated in vivo and in vitro. Potential signaling networks in different cell types induced by apigenin were identified, suggesting that the molecular mechanisms of apigenin in cardiometabolic diseases vary with cell types. Additionally, the mechanisms of apigenin-induced biological response in different cardiometabolic diseases were analyzed, including obesity, diabetes, hypertension and cardiovascular diseases. This review provides novel insights into the potential role of apigenin in cardiometabolic diseases.